Application of fuzzy comprehensive evaluation method in network information security assessment of electric power enterprises - Daoyuan LIU; Keda SUN; Junliang ZHOU; Haidong FAN (Dianxin kexue)
Nowadays,electric power enterprises have realized the operation and production of information technology,and the importance of network information security evaluation is more and more obvious.Two-level fuzzy comprehensive evaluation method was used to evaluate the security level of network information security system of power enterprises based on PRDD model,and Delphi method was used to determine the weight coefficients of various factors of network security of power enterprises in the evaluation process.Through objective analysis of the evaluation results,the network credit of power enterprises was found out.The prominent problems existing in the informa tion security system should be solved and the corresponding security reinforcement scheme should be formulated.The validation results show that the optimized network information security model is more robust,practicability and operability are significantly improved,which effectively improve the network information security level of power enterprises,and can be used as a favorable reference for the construction of network information security of other power enterprises.